The Influence of School Climate on Student Engagement Through the Mediating Role of Growth Mindset Among Vocational High School Students - Mutiara Wardhani; Rahmi Lubis; Yudistira Fauzy Indrawan (International Journal of Educational Practice and Policy, 2026)
This study aims to examine the effect of school climate on student engagement with growth mindset as a mediating variable among vocational high school students. The research employed a quantitative explanatory design involving 220 students selected from a population of 492 using proportionate stratified random sampling. Data were collected using validated Likert-scale instruments, including the Student Engagement Scale (α = 0.927), School Climate Scale (PACE-33), and Growth Mindset Scale (α = 0.793), and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results showed that all constructs met validity and reliability criteria (AVE > 0.50; CR and CA > 0.70), and the model showed good fit (SRMR = 0.055). Hypothesis testing revealed that school climate significantly affects student engagement (β = 0.162; t = 4.569; p < 0.05) and growth mindset (β = 0.190; t = 7.661; p < 0.05), while growth mindset significantly influences student engagement (β = 0.195; t = 8.520; p < 0.05). Additionally, growth mindset was found to partially mediate the relationship between school climate and student engagement, with a stronger indirect effect (β = 0.312; p < 0.05) compared to the direct effect. The model explains 55% of the variance in growth mindset and 61% in student engagement, indicating moderate to strong predictive power. These findings show that both environmental and psychological factors play a role in enhancing student engagement.